2015
DOI: 10.2174/1567201812666150326110821
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Spray Dried Microparticles for Pulmonary Delivery of Antifungal Drug

Abstract: Invasive pulmonary aspergillosis is a life threatening fungal infection mainly caused by Aspergillus species. Available treatment strategy against pulmonary aspergillosis is having very limited applicability, due to its toxicity and low circulation half-life. Pulmonary drug delivery is one of the strategies that can minimize these pitfalls. In the present study, polymeric and lipidic nanoparticles of amphotericin B were prepared by spray drying technique using hydroxypropylmethylcellulose (HPMC) and stearylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…AmB-loaded NLCs prepared from Sta and OA were developed for pulmonary delivery yielding spray-dried microparticles suitable for dry powder inhaler [203]. This formulation provided sustained drug release (88.2% up to 40 h), achieving localized action in the lungs, and reduced drug nephrotoxic side effects after pulmonary administration to rats, according to pharmacokinetic parameters, organ distribution studies, histopathology, and hematological data [203].…”
Section: Solid Lipid Nanoparticles and Nanostructured Lipid Carriersmentioning
confidence: 99%
“…AmB-loaded NLCs prepared from Sta and OA were developed for pulmonary delivery yielding spray-dried microparticles suitable for dry powder inhaler [203]. This formulation provided sustained drug release (88.2% up to 40 h), achieving localized action in the lungs, and reduced drug nephrotoxic side effects after pulmonary administration to rats, according to pharmacokinetic parameters, organ distribution studies, histopathology, and hematological data [203].…”
Section: Solid Lipid Nanoparticles and Nanostructured Lipid Carriersmentioning
confidence: 99%
“…To avoid the conventional routes of administration and to enhance the local drug bioavailability, another alternative is found by inhalation AmB particles to target local action in the lungs. A recent study has showed interest in using a pulmonary route for administering microparticles and lipid complexes [19]. The results showed a good pulmonary deposition and a lower rate of active substance in the kidney leading to a reduction of drug nephrotoxicity and an improvement of fungal activity, approximately 1.5-times better than the marketed intravenous preparations.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a good pulmonary deposition and a lower rate of active substance in the kidney leading to a reduction of drug nephrotoxicity and an improvement of fungal activity, approximately 1.5-times better than the marketed intravenous preparations. Pharmacokinetic and organ distribution studies showed that the pulmonary administration may be favorable for a good efficiency by local action [19].…”
Section: Introductionmentioning
confidence: 99%
“…They are formulated as sprays, creams, solutions, ointment, shampoos, vaginal tablets, oral medicines, and injections [3]. The duration of treatment depends on kind of fungal infection, health problems of the infected patient, problems associated with immune system and types of formulations.…”
Section: Introductionmentioning
confidence: 99%